Colony polymerase chain reaction of heme-accumulating bacteria. (April 2015) - Pardesi, Bikiran; Tompkins, Geoffrey R.
Abstract: Colony PCR of anaerobic black-pigmenting Bacteroidetes species Porphyromonas gingivalis and Prevotella intermedia was modified by addition of bovine serum albumin to reverse the inhibitory action of accumulated heme.